2022
DOI: 10.2337/dc22-1399
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Carbamylation and Anemia on HbA1c’s Association With Renal Outcomes in Patients With Diabetes and Chronic Kidney Disease

Abstract: OBJECTIVE Glycated hemoglobin (HbA1c) can predict risk for microvascular complications in patients with diabetes. However, HbA1c’s reliability in chronic kidney disease (CKD) has been questioned, with concerns including competition from another posttranslational protein modification, carbamylation, acting on the same amino groups as glycation, and anemia with reduced erythrocyte lifespans leading to altered glycation accumulation. We investigated whether carbamylation and anemia modify the im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…This finding reinforces what has been documented in the medical literature, where cardiovascular diseases emerge as the primary cause of morbidity and mortality in individuals with T2D. 48 …”
Section: Discussionsupporting
confidence: 91%
“…This finding reinforces what has been documented in the medical literature, where cardiovascular diseases emerge as the primary cause of morbidity and mortality in individuals with T2D. 48 …”
Section: Discussionsupporting
confidence: 91%
“…In addition, the bias of the results of four common hemoglobin variants (Hb S, Hb C, Hb D, and Hb E) did not exceed the permitted range. This demonstrates that enzymatic methods are less susceptible to interference from hemoglobin variants than ion-exchange high-performance liquid chromatography, as previously reported 14 . The enzymatic assay is based on measuring the percentage of HbA 1c in total hemoglobin.…”
Section: Discussionsupporting
confidence: 85%
“…HbA 1c is a product formed when hemoglobin and glucose combine in red blood cells. Therefore, any factors that cause changes in the quantity and quality of hemoglobin, such as hemoglobinopathies, derived hemoglobin, abnormalities in the erythrocyte survival lifespan, and drugs, can interfere with the HbA 1c assay [13][14][15][16] . Our results indicated that routine interferences such as lipemia, hemolysis, jaundice, and vitamin C did not affect the BS-600M enzymatic assay.…”
Section: Discussionmentioning
confidence: 99%
“…eGFR is known to be critical to the diagnosis and progression of DKD. Higher HbA1c was associated with an increased risk of CKD progression in patients with diabetes and remained an independent risk factor for adverse renal outcomes in patients with diabetes and CKD in patients with low carbamylation levels and no anemia [ 31 ]. According to a systematic review and meta-analysis of 20 cohorts, when HbA1c increased by 1%, the risk for DKD increased by 17% [ 32 ].…”
Section: Discussionmentioning
confidence: 99%